Asymmetric responses of soil organic carbon stability to shifting dominance of pH-mediated metal-bound organic carbon - Huiying Wen; Fei Yang; Zheng Sun; Ziyi Miao; Jin Hu; Ganlin Zhang (Communications Earth & Environment)
Abstract Association with reactive metal (hydr)oxides is critical for soil organic carbon (SOC) stabilization. However, direct evidence is lacking on how shifting dominance of different metal-bound organic carbon within soil profile mediates SOC stability. Here we leverage a natural experiment comprising 16 soil profiles (~200 cm) sampled along a 1,500 km climatic gradient from semi-humid to semi-arid. We indicate that the response of SOC chemical stability (acid hydrolysis for recalcitrant organic carbon determination) to metal-bound organic carbon is asymmetric, meaning that metal-bound organic carbon dominating recalcitrant organic carbon does not strictly follow the pattern of greater content equating to stronger effect. Soil pH mediates the shift in dominance from iron to calcium phases over the range of 7.2 to 7.6, thereby regulating their respective impact on recalcitrant organic carbon. Our findings elucidate the key behavior of metal-bound organic carbon (especially calcium-bound organic carbon), in maintaining SOC stability under soil pH regulation.